Nursing Workloads and Psychological Empowerment in Hospitals: Structural Equations Modeling - Parvin Ebrahimi; Zainab Malmoon; Rouhollah Zaboli (Baqiyatallah University of Medical Sciences, 2017)
Background: The high workload of nurses in hospitals has been identified as a patient safety and worker stress problem. Psychological empowerment is a motivational concept demonstrated in four dimensions: meaning, competence, self-determination, and impact. Objective: This study investigated the relationship between nurses' workloads and psychological empowerment using structural equations modeling (SEM). Methods: This descriptive correlation study was conducted using SEM. The study was conducted at 17 public hospitals affiliated with Iran University of Medical Sciences (IUMS) in the city of Tehran. The population study was nurses employed in critical care departments. Two questionnaires were used to gather data: the NASA and the Psychological Empowerment Questionnaires. Differences in categorical variables were analyzed using one-way analysis of variance (ANOVA). Confirmatory factor analyses were used to confirm the relationships between latent variables and indicator variables; SEM was used to find the direct and indirect effects of nurse's workload on psychological empowerment. Data analyses were performed using SPSS 18, and all models were tested in LISREL 8.8. Results: Correlations among indicators of nurse's workload showed that highest correlations were performances (0.61), and the highest correlations among psychological empowerment were competence (0.03). The overall correlations among nursing workloads and psychological empowerment were 0.74. The proposed structural model fit was acceptable (χ2 = 525.5, df = 89, RMSEA = 0.13, GFI = 0.91). Conclusion: Increasing the workload of nurses in hospitals will better engage the nurses and allow them to face new problems they encounter in their jobs.